Preparation and application of solid-state composite electrolyte containing modified lithium ferrous silicate filler

Solid-state composite electrolyte is prepared by combining sodium-doped modified lithium ferrous silicate filler with polymer, which solves the low conductivity and safety problems of electrolytes in lithium-ion batteries and improves the cycling performance and energy density of the battery.

CN119118143APending Publication Date: 2024-12-13NANJING UNIV OF SCI & TECH
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411141378.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-20
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

The organic liquid electrolyte commonly used in lithium-ion batteries has the disadvantages of leakage, toxicity, and flammability, and the ionic conductivity and electronic conductivity of lithium ferrous silicate as a positive electrode material are relatively low, which limits its application.

Method used

Solid-state composite electrolyte is prepared by combining sodium-doped modified lithium ferrous silicate filler with polymer. Sodium-doped lithium ferrous silicate filler is prepared by ball milling and calcining, and is uniformly mixed with the polymer substrate to form high ionic conductivity. Compound electrolyte of rate and mechanical strength.

Benefits of technology

It improves lithium ion conductivity and electrolyte cycling performance, enhances the interface contact between electrolyte and lithium metal, and improves the safety performance and energy density of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119118143A_ABST
    Figure CN119118143A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of a solid electrolyte of a lithium ion battery, and discloses a modification and preparation method of a lithium ferrous silicate material, and the lithium ferrous silicate material is used as an inorganic filler and is mixed with a poly (vinylidene fluoride-co-hexafluoropropylene) (PVDF-HFP) polymer matrix to prepare a solid composite electrolyte. According to the invention, sodium doping is carried out on the lithium ferrous silicate material, and doped sodium replaces part of lithium sites, so that a lithium ion migration channel is widened, and the lithium ion conductivity of the lithium ferrous silicate is enhanced; the modified lithium ferrous silicate is used as an active filler and is combined with a polymer to prepare the composite electrolyte (CPE), so that on one hand, the mechanical strength of a polymer matrix is enhanced, and on the other hand, the migration path of lithium ions is widened, thereby remarkably improving the ionic conductivity and the lithium ion transference number of the composite electrolyte; the composite electrolyte has good interface contact with an electrode plate, and the cycling stability of the battery can be further improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of lithium ion battery solid electrolytes, and specifically relates to the modification of lithium ferrous silicate materials and the preparation and application of solid electrolytes. Background Art

[0002] Lithium-ion batteries have the advantages of high energy density, high operating voltage, and long service life, and have attracted widespread attention. Since their commercialization in 1991, they have been widely used in many electronic products such as mobile phones and computers. Electrolyte is an important component of the battery structure. Currently, most lithium-ion batteries on the market are based on organic liquid electrolytes, which have the disadvantages of leakage, toxicity, and flammability. By using solid materials as electrolytes, the above problems can be effectively avoided and the safety performance of the battery can be improved.

[0003] Lithium ferrous silicate is often used as a cathode material for lithium-ion batteries. It has the advantages of high theoretical capacity, low price, and environmental friendliness, but its low ionic conductivity and electronic conductivity are one of the factors that limit its use as a cathode material for lithium-ion batteries. Some Na elements are added to lithium ferrous silicate to replace some Li sites. Since the atomic radius of Na is larger than that of Li, the addition of Na can expand the lattice parameters of lithium ferrous silicate, broaden the lithium ion migration channel, and reduce the lithium ion migration barrier, thereby improving the lithium ion conductivity.

[0004] Solid electrolytes can be divided into inorganic solid electrolytes, solid polymer electrolytes (SPE) and composite solid electrolytes (CPE). Among them, inorganic solid electrolytes have higher ionic conductivity and better mechanical properties, but poor contact with the interface; polymer electrolytes have certain flexibility and good interface contact, but low ionic conductivity. Organic-inorganic composite electrolytes combine polymer electrolytes with inorganic fillers. They have the advantages of high ionic conductivity of inorganic electrolytes and retain the excellent interface contact performance of polymer electrolytes. They are the mainstream direction of solid electrolyte research at present.

[0005] The inorganic fillers used in organic-inorganic composite electrolytes are basically divided into two categories: inert fillers and active fillers. Inert fillers can weaken the interaction between polymer segments, reduce crystallinity, and promote the dissociation of lithium salts, which is beneficial to Li + The active filler can be used as an inorganic solid electrolyte. In addition to reducing the crystallinity of the polymer and promoting the dissociation of lithium salts, it can also provide a + In the composite electrolyte with active fillers, Li + There are different migration modes in different regions: (1) migration through the polymer inside the polymer, (2) migration through vacancies or gaps in the active filler, and (3) migration at the interface between the filler and the polymer. Summary of the invention

[0006] In order to solve the above problems, the present invention discloses a sodium-doped modified lithium ferrous silicate filler, a preparation method and application of a solid composite electrolyte containing the sodium-doped modified lithium ferrous silicate filler.

[0007] To achieve the above object, the technical solution of the present invention is as follows:

[0008] The invention discloses a method for preparing a sodium-doped modified lithium ferrous silicate filler, comprising the following steps:

[0009] S1-1, ball-milling lithium carbonate, sodium carbonate, ferrous oxalate dihydrate and silicon dioxide to obtain a precursor powder;

[0010] S1-2, put the precursor powder into a tube furnace and calcine to obtain Li 2-x Na x FeSiO4(LNFS) filler;

[0011] S1-3, adding anhydrous ethanol to the LNFS filler, ball-milling and drying to obtain a sodium-doped modified lithium ferrous silicate filler LNFS;

[0012] Where x is 0-0.3.

[0013] Furthermore, in step S1-1, lithium carbonate, sodium carbonate, ferrous oxalate dihydrate, and silicon dioxide are measured according to a molar ratio of Li:Na:Fe:Si=(2-x):x:1:1; the ball milling speed is 400-500 rpm, and the ball milling time is 12-24 h.

[0014] Furthermore, in step S1-2, the calcination temperature is 600-800°C, the heating rate is 5-10°C / min; the calcination time is 3-10h; and the calcination atmosphere is one or both of argon and nitrogen.

[0015] Furthermore, in step S1-3, the mass percentage of LNFS filler and anhydrous ethanol is 50-100wt%; the ball milling speed is 400-500rpm, and the ball milling time is 12-24h.

[0016] The present invention also provides a sodium-doped modified lithium ferrous silicate filler LNFS prepared by the preparation method as described above.

[0017] The present invention also provides a method for preparing a solid composite electrolyte containing the sodium-doped modified lithium ferrous silicate filler as described above, comprising the following steps:

[0018] S2-1, dissolving the polymer, lithium salt, and the sodium-doped modified lithium ferrous silicate filler LNFS as described above in an organic solvent, and uniformly mixing them to obtain a composite electrolyte slurry;

[0019] S2-2, pouring the obtained composite electrolyte slurry into a polytetrafluoroethylene (PTFE) mold, and drying it in a vacuum oven to obtain a solid composite electrolyte (CPE) with uniform thickness.

[0020] Furthermore, in step S2-1, the mass percentage of the sodium-doped modified lithium ferrous silicate filler LNFS to the polymer is 10-100wt%; the mass percentage of the polymer to the lithium salt is 50-110wt%; and the mass percentage of the polymer to the organic solvent is 3-5wt%.

[0021] Furthermore, the polymer is poly(vinylidene fluoride-co-hexafluoropropylene) (PVDF-HFP); the organic solvent is N,N-dimethylformamide (DMF); and the lithium salt is one or both of lithium bis(trifluoromethanesulfonyl imide) (LiTFSI) and lithium bis(difluorosulfonyl imide) (LiFSI).

[0022] Furthermore, in step S2-2, the thickness of the obtained solid composite electrolyte is 80-110 μm.

[0023] Furthermore, in step S2-1, the uniform mixing method is at least one of magnetic stirring and ball milling; the magnetic stirring time and the ball milling mixing time are 12-24h.

[0024] Furthermore, in step S2-2, the drying temperature in the vacuum oven is 60-80°C, and the drying time is 24-48h.

[0025] The composite electrolyte obtained in step S2-2 was cut into discs with a diameter of 16 mm, and a button cell was assembled using a LIR2025 battery shell to test the electrochemical performance. Among them, the blocking electrode (SS / CPE / SS) was used for the AC impedance spectrum test, and the assembly order was: stainless steel sheet / electrolyte / stainless steel sheet / shrapnel; the assembly order of the symmetrical battery (Li / CPE / Li) was: lithium sheet / electrolyte / lithium sheet / gasket / shrapnel; the assembly order of the full battery (LFP / CPE / Li) was: lithium iron phosphate positive electrode / electrolyte / lithium sheet / gasket / shrapnel.

[0026] The beneficial effects of the present invention are:

[0027] The invention discloses a sodium-doped modified lithium ferrous silicate filler, a preparation method of a solid composite electrolyte containing the sodium-doped modified lithium ferrous silicate filler and an application thereof; lithium ferrous silicate itself has low ionic conductivity and electronic conductivity, and the incorporation of Na occupies part of the Li site, expands the lattice of lithium ferrous silicate, and broadens the Li + The transmission channel of lithium ions is improved, thereby improving the lithium ion conductivity. Using LNFS as a filler and combining it with a polymer substrate to prepare a composite electrolyte, the mechanical strength of the composite electrolyte is enhanced, and the ionic conductivity and cycle performance of the composite electrolyte are improved. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 A flow chart of a method for preparing a sodium-doped Li2FeSiO4 solid electrolyte filler and a composite electrolyte preparation process provided by the present invention;

[0029] Figure 2 This is a scanning electron microscope image of LNFS-0.1 prepared in Example 1 of the present invention;

[0030] Figure 3 This is a scanning electron microscope image of LNFS-0.2 prepared in Example 2 of the present invention;

[0031] Figure 4 This is a scanning electron microscope image of LNFS-0.3 prepared in Example 3 of the present invention;

[0032] Figure 5 The X-ray diffraction patterns of LNFS prepared in Example 1, Example 2, and Example 3 of the present invention;

[0033] Figure 6 is a scanning electron microscope image of the PVDF-HFP based composite electrolyte prepared in Example 4 of the present invention;

[0034] Figure 7 is a scanning electron microscope cross-sectional view of the PVDF-HFP-based composite electrolyte prepared in Example 4 of the present invention;

[0035] Figure 8 This is a long cycle performance diagram of a symmetrical battery (Li / CPE / Li) of a PVDF-HFP-based composite electrolyte prepared in Example 4 of the present invention;

[0036] Fig. 9 This is a cycle performance diagram of a full battery (LFP / CPE / Li) of the PVDF-HFP composite electrolyte obtained in Example 4 of the present invention;

[0037] Fig.10 This is a rate performance diagram of a full battery (LFP / CPE / Li) of a PVDF-HFP-based composite electrolyte obtained in Example 4 of the present invention;

[0038] Fig.11 The AC impedance spectra of the blocked electrodes (SS / CPE / SS) of the PVDF-HFP-based composite electrolytes prepared in Examples 4, 5 and 6 of the present invention;

[0039] Fig.12 The AC impedance spectra of the blocked electrodes (SS / CPE / SS) of the PVDF-HFP-based composite electrolytes prepared in Examples 4, 7 and 8 of the present invention;

[0040] Fig.13 X-ray diffraction patterns of LFS and LNFS-0.4 prepared in Comparative Examples 1 and 2 of the present invention;

[0041] Fig.14 This is a long cycle performance diagram of the PVDF-HFP-based polymer electrolyte symmetric battery (Li / SPE / Li) prepared in Comparative Example 3 of the present invention;

[0042] Fig.15 The AC impedance spectra of the blocked electrodes (SS / CPE / SS) of the PVDF-HFP-based polymer electrolytes and composite electrolytes prepared in Comparative Examples 3, 4 and 5 of the present invention; DETAILED DESCRIPTION

[0043] The present invention will be further explained below in conjunction with the accompanying drawings and specific embodiments. It should be understood that the following specific embodiments are only used to illustrate the present invention and are not used to limit the scope of the present invention.

[0044] Example 1

[0045] Li 1.9 Na 0.1 Preparation of FeSiO4(LNFS-0.1).

[0046] Preparation steps: Weigh 2.2112g lithium carbonate, 0.159g sodium carbonate, 5.3958g ferrous oxalate dihydrate, and 1.8027g silicon dioxide, put them into a ball mill, and mill them in a planetary ball mill at 400rpm for 12h to obtain a uniformly mixed precursor. Put the precursor powder into an alumina crucible, sinter it in a tube furnace, pass inert gas Ar, set the heating rate to 5℃ / min, the sintering temperature to 750℃, and the calcination time to 10h to obtain LNFS powder. Put the sintered powder into a ball mill, add 50wt% of anhydrous ethanol by mass, put it into a planetary ball mill at 400rpm for 12h, and put it in an 80℃ oven for drying for 12h to obtain LNFS-0.1.

[0047] The scanning electron microscope image of LNFS-0.1 obtained in Example 1 is as follows: Figure 2 As shown in the figure, it can be measured that the particle size of the prepared LNFS-0.1 is 4.7 μm.

[0048] Example 2

[0049] Li 1.8 Na 0.2 Preparation of FeSiO4(LNFS-0.2).

[0050] Preparation steps: Weigh 2.0948g lithium carbonate, 0.318g sodium carbonate, 5.3958g ferrous oxalate dihydrate, and 1.8027g silicon dioxide, put them into a ball mill, and mill them in a planetary ball mill at 400rpm for 12h to obtain a uniformly mixed precursor. The precursor powder is placed in an alumina crucible, sintered in a tube furnace, inert gas Ar is introduced, the heating rate is set to 5℃ / min, the sintering temperature is 750℃, and the calcination time is 10h to obtain LNFS powder. The sintered powder is placed in a ball mill, 50wt% of anhydrous ethanol is added, and the mixture is placed in a planetary ball mill at 400rpm for 12h, and then dried in an oven at 80℃ for 12h to obtain LNFS-0.2.

[0051] The scanning electron microscope image of LNFS-0.2 obtained in Example 2 is as follows: Figure 3 As shown in the figure, it can be measured that the particle size of the prepared LNFS-0.2 is 6.7 μm.

[0052] Example 3

[0053] Li 1.7 Na 0.3 Preparation of FeSiO4(LNFS-0.3).

[0054] Preparation steps: Weigh 1.9784g lithium carbonate, 0.477g sodium carbonate, 5.3958g ferrous oxalate dihydrate, and 1.8027g silicon dioxide, put them into a ball mill, and mill them in a planetary ball mill at 400rpm for 12h to obtain a uniformly mixed precursor. The precursor powder is placed in an alumina crucible, sintered in a tube furnace, inert gas Ar is introduced, the heating rate is set to 5℃ / min, the sintering temperature is 750℃, and the calcination time is 10h to obtain LNFS powder. The sintered powder is placed in a ball mill, 50wt% of anhydrous ethanol is added, and the mixture is placed in a planetary ball mill at 400rpm for 12h, and then dried in an oven at 80℃ for 12h to obtain LNFS-0.3.

[0055] The scanning electron microscope image of LNFS-0.3 obtained in Example 3 is as follows: Figure 4 As shown in the figure, it can be measured that the particle size of the prepared LNFS-0.3 is 3.4 μm.

[0056] The X-ray diffraction patterns of LNFS obtained in Example 1, Example 2 and Example 3 are as follows: Figure 5 As shown in the figure, it can be analyzed that the X-ray diffraction pattern of the prepared LNFS is consistent with the standard PDF card. With the incorporation of Na, the obtained X-ray diffraction pattern gradually shifts to the direction of small angles, indicating that after the incorporation of Na, the lattice constant becomes larger.

[0057] Example 4

[0058] Preparation of PVDF-HFP based composite electrolytes.

[0059] Preparation steps: Weigh 0.5g PVDF-HFP, 0.55g LiTFSI, 0.1g LNFS-0.1, add 15mL DMF, and mill in a planetary ball mill for 12h to obtain a composite electrolyte slurry. Pour the electrolyte slurry into a PTFE mold and dry it in a vacuum oven at 80℃ for 36h to obtain a solid composite electrolyte, which is recorded as 20LNFS-0.1.

[0060] The scanning electron microscope image of the composite electrolyte obtained in Example 4 is as follows Figure 6 As shown in the figure, it can be seen that the spherical structure of PVDF-HFP is evenly distributed.

[0061] The scanning electron microscope cross-sectional view of the composite electrolyte obtained in Example 4 is as follows Figure 7 As shown in the figure, it can be measured that the thickness of the prepared composite electrolyte is about 100 μm.

[0062] The composite electrolyte obtained in Example 4 was assembled into a symmetrical battery (Li / CPE / Li), and the lithium symmetric long cycle performance obtained by testing was shown in the figure below: Figure 8 As shown in the figure, it can be seen that the prepared composite electrolyte assembled symmetrical battery (Li / CPE / Li) has a high conductivity at room temperature of 0.1 mA / cm 2 It can stably cycle for more than 500 hours at a current density of 0.05V with an overpotential of 0.05V.

[0063] The composite electrolyte obtained in Example 4 was assembled into a full battery (LFP / CPE / Li), and the cycle performance obtained by testing was shown in the figure below: Fig. 9 As shown in the figure, it can be seen that the capacity retention rate of the full battery (LFP / CPE / Li) assembled with the prepared composite electrolyte is 96.3% after 100 cycles at a rate of 0.5C at room temperature.

[0064] The composite electrolyte obtained in Example 4 was assembled into a full battery (LFP / CPE / Li), and the rate performance obtained by testing was shown in the figure below: Fig.10 As shown in the figure, it can be seen that the prepared composite electrolyte assembled full battery (LFP / CPE / Li) has good cycle stability at several test rates at room temperature. The discharge capacity at a rate of 1C is 142mAh / g. When it returns from 1C to 0.1C, the discharge capacity is 158.4mAh / g, which is 97.1% of the initial discharge capacity.

[0065] Example 5

[0066] Preparation of PVDF-HFP based composite electrolytes.

[0067] Preparation steps: Weigh 0.5g PVDF-HFP, 0.55g LiTFSI, 0.1g LNFS-0.2, add 15mL DMF, and mill in a planetary ball mill for 12h to obtain a composite electrolyte slurry. Pour the electrolyte slurry into a PTFE mold and dry it in a vacuum oven at 80℃ for 36h to obtain a solid composite electrolyte, which is recorded as 20LNFS-0.2.

[0068] Example 6

[0069] Preparation of PVDF-HFP based composite electrolytes.

[0070] Preparation steps: Weigh 0.5g PVDF-HFP, 0.55g LiTFSI, 0.1g LNFS-0.3, add 15mL DMF, and mill in a planetary ball mill for 12h to obtain a composite electrolyte slurry. Pour the electrolyte slurry into a PTFE mold and dry it in a vacuum oven at 80℃ for 36h to obtain a solid composite electrolyte, which is recorded as 20LNFS-0.3.

[0071] The composite electrolytes obtained in Example 4, Example 5, and Example 6 were assembled with blocking electrodes, and the AC impedance spectra obtained by testing were as follows: Fig.11 As shown in the figure, it can be concluded that when the filler is 20wt% LNFS-0.1, the impedance is 6.39Ω; when the filler is 20wt% LNFS-0.2, the impedance is 8.81Ω; when the filler is 20wt% LNFS-0.3, the impedance is 8.71Ω. The calculated ionic conductivities are 6.30×10 -4 S / cm, 5.03×10 -4 S / cm, 4.40×10 -4 S / cm.

[0072] Example 7

[0073] Preparation of PVDF-HFP based composite electrolytes.

[0074] Preparation steps: Weigh 0.5g PVDF-HFP, 0.55g LiTFSI, 0.05g LNFS-0.1, add 15mL DMF, and mill in a planetary ball mill for 12h to obtain a composite electrolyte slurry. Pour the electrolyte slurry into a PTFE mold and dry it in a vacuum oven at 80℃ for 36h to obtain a solid composite electrolyte, which is recorded as 10LNFS-0.1.

[0075] Example 8

[0076] Preparation of PVDF-HFP based composite electrolytes.

[0077] Preparation steps: Weigh 0.5g PVDF-HFP, 0.55g LiTFSI, 0.15g LNFS-0.1, add 15mL DMF, and mill in a planetary ball mill for 12h to obtain a composite electrolyte slurry. Pour the electrolyte slurry into a PTFE mold and dry it in a vacuum oven at 80℃ for 36h to obtain a solid composite electrolyte, which is recorded as 30LNFS-0.1.

[0078] The composite electrolytes obtained in Example 4, Example 7, and Example 8 were assembled with blocking electrodes, and the AC impedance spectra obtained by testing were as follows: Fig.12 As shown in the figure, it can be concluded that when the filler is 10wt% LNFS-0.1, the impedance is 7.24Ω; when the filler is 20wt% LNFS-0.1, the impedance is 6.39Ω; when the filler is 30wt% LNFS-0.1, the impedance is 7.91Ω. The calculated ionic conductivities are 5.09×10 -4 S / cm, 6.30×10 -4 S / cm, 4.78×10 -4 S / cm.

[0079] Comparative Example 1

[0080] Preparation of Li2FeSiO4 (LFS).

[0081] Preparation steps: Weigh 2.3275g lithium carbonate, 5.3958g ferrous oxalate dihydrate, and 1.8027g silicon dioxide, put them into a ball mill, and ball mill them in a planetary ball mill at 400rpm for 12h to obtain a uniformly mixed precursor. Put the precursor powder into an alumina crucible, sinter it in a tube furnace, pass inert gas Ar, set the heating rate to 5℃ / min, the sintering temperature to 750℃, and the calcination time to 10h to obtain LFS powder. Put the sintered powder into a ball mill, add 50wt% of anhydrous ethanol by mass, put it into a planetary ball mill at 400rpm for 12h, and put it in an 80℃ oven to dry for 12h to obtain LFS.

[0082] Comparative Example 2

[0083] Li 1.6 Na 0.4 Preparation of FeSiO4(LNFS-0.4).

[0084] Preparation steps: Weigh 1.8620g lithium carbonate, 0.636g sodium carbonate, 5.3958g ferrous oxalate dihydrate, and 1.8027g silicon dioxide, put them into a ball mill, and mill them in a planetary ball mill at 400rpm for 12h to obtain a uniformly mixed precursor. The precursor powder is placed in an alumina crucible, sintered in a tube furnace, inert gas Ar is introduced, the heating rate is set to 5℃ / min, the sintering temperature is 750℃, and the calcination time is 10h to obtain LNFS powder. The sintered powder is placed in a ball mill, 50wt% of anhydrous ethanol is added, and the mixture is placed in a planetary ball mill at 400rpm for 12h, and then dried in an oven at 80℃ for 12h to obtain LNFS-0.4.

[0085] The X-ray diffraction patterns of LFS and LNFS-0.4 obtained in Comparative Example 1 and Comparative Example 2 are as follows: Fig.13 The prepared LFS and LNFS-0.4 are consistent with the standard PDF card. Compared with LFS, the X-ray diffraction pattern of LNFS-0.4 shifts to a smaller angle.

[0086] Comparative Example 3

[0087] Preparation of PVDF-HFP based polymer electrolyte.

[0088] Preparation steps: Weigh 0.5g PVDF-HFP and 0.55g LiTFSI, add 15mL DMF, and mill in a planetary ball mill for 12h to obtain a polymer electrolyte slurry. Pour the electrolyte slurry into a PTFE mold and dry it in a vacuum oven at 80℃ for 36h to obtain a solid polymer electrolyte, which is recorded as 1.1LiTFSI.

[0089] The polymer electrolyte obtained in Comparative Example 3 was assembled into a symmetrical battery (Li / SPE / Li), and the lithium symmetric long cycle performance obtained by testing was shown in the figure below: Fig.14 The symmetric lithium battery with PVDF-HFP-based polymer electrolyte at room temperature is shown in Figure 2. 2 After 300 cycles at a current density of , a short circuit occurred, and the cycle performance was poor.

[0090] Comparative Example 4

[0091] Preparation of PVDF-HFP based composite electrolytes.

[0092] Preparation steps: Weigh 0.5g PVDF-HFP, 0.55g LiTFSI, 0.1g LFS, add 15mL DMF, and mill in a planetary ball mill for 12h to obtain a composite electrolyte slurry. Pour the electrolyte slurry into a PTFE mold and dry it in a vacuum oven at 80℃ for 36h to obtain a solid composite electrolyte, recorded as 20LFS.

[0093] Comparative Example 5

[0094] Preparation of PVDF-HFP based composite electrolytes.

[0095] Preparation steps: Weigh 0.5g PVDF-HFP, 0.55g LiTFSI, 0.1g LNFS-0.4, add 15mL DMF, and mill in a planetary ball mill for 12h to obtain a composite electrolyte slurry. Pour the electrolyte slurry into a PTFE mold and dry it in a vacuum oven at 80℃ for 36h to obtain a solid composite electrolyte, which is recorded as 20LNFS-0.4.

[0096] The AC impedance spectra of the PVDF-HFP-based polymer electrolyte and composite electrolyte assembled blocking electrode prepared in Comparative Examples 3, 4 and 5 are shown in FIG. Fig.15 As shown in the figure, it can be analyzed that the impedance of the polymer electrolyte is 26.44Ω, the impedance is 8.02Ω when the filler is 20wt% LFS, and the impedance is 15.38Ω when the filler is 20wt% LNFS-0.4; the ionic conductivity is 1.58×10 -4 S / cm, 4.03×10 -4 S / cm, 2.85×10 -4 S / cm. Combining Examples 4, 5, and 6, it can be analyzed that the addition of fillers will increase the ionic conductivity, but adding too much Na into the fillers will lead to a decrease in ionic conductivity.

[0097] In summary, the Na-doped Li2FeSiO4 prepared in the present invention is used as a filler for the composite electrolyte, which improves the ionic conductivity of the PVDF-HFP-based electrolyte and improves the interface contact between the electrolyte and Li metal, further improving the cycle performance.

[0098] It should be noted that the above content merely illustrates the technical idea of ​​the present invention and cannot be used to limit the protection scope of the present invention. For ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications all fall within the protection scope of the claims of the present invention.

Claims

1. A method for preparing sodium-doped modified lithium ferrous silicate filler, characterized in that: The following steps are involved: S1-1, lithium carbonate, sodium carbonate, ferrous oxalate dihydrate, and silicon dioxide are ball-milled to obtain a precursor powder; S1-2, the precursor powder is placed in a tubular furnace and calcined to obtain Li 2-x Na x FeSiO4 filler; S1-3, in Li 2-x Na x Anhydrous ethanol was added to the FeSiO4 filler, and the mixture was ball-milled and dried to obtain sodium-doped modified lithium ferrous silicate filler Li 2-x Na x FeSiO4; Where x is 0-0.

3.

2. The method for preparing a sodium-doped modified lithium ferrous silicate filler according to claim 1, characterized in that: step In S1-1, lithium carbonate, sodium carbonate, ferrous oxalate dihydrate, and silicon dioxide are measured according to the molar ratio of Li:Na:Fe:Si=(2-x):x:1:1; the ball milling speed is 400-500 rpm; and the ball milling time is 12-24 h.

3. The method for preparing a sodium-doped modified lithium ferrous silicate filler according to claim 1, characterized in that: step In S1-2, the calcination temperature is 600-800°C; the heating rate is 5-10°C / min; the calcination time is 3-10h; and the calcination atmosphere is one or both of argon and nitrogen.

4. The method for preparing a sodium-doped modified lithium ferrous silicate filler according to claim 1, characterized in that: step In S1-3, Li 2-x Na x The mass percentage of FeSiO4 filler and anhydrous ethanol is 50-100wt%; the ball milling speed is 400-500rpm; and the ball milling time is 12-24h.

5. A method for preparing a solid composite electrolyte containing sodium-doped modified lithium ferrous silicate filler prepared by the preparation method according to any one of claims 1 to 4, characterized in that: The following steps are involved: S2-1, polymer, lithium salt, sodium doped modified lithium ferrous silicate filler according to any one of claims 1 to 4 Li 2-x Na x FeSiO4 is dissolved in an organic solvent and uniformly mixed to obtain a composite electrolyte slurry; S2-2. The obtained composite electrolyte slurry is poured into a polytetrafluoroethylene mold, and dried in a vacuum oven to obtain a solid composite electrolyte with uniform thickness.

6. The method for preparing a solid composite electrolyte containing sodium-doped modified lithium ferrous silicate filler according to claim 5, characterized in that: In step S2-1, sodium doped modified lithium ferrous silicate filler Li 2-x Na x The mass percentage of FeSiO4 and polymer is 10-100wt%; the mass percentage of lithium salt and polymer is 50-110wt%; the mass percentage of polymer and organic solvent is 3-5wt%.

7. The method for preparing a solid composite electrolyte containing sodium-doped modified lithium ferrous silicate filler according to claim 6, characterized in that: The polymer is poly(vinylidene fluoride-co-hexafluoropropylene); the organic solvent is N,N-dimethylformamide; and the lithium salt is one or both of bistrifluoromethanesulfonyl imide lithium and bisdifluorosulfonyl imide lithium.

8. The method for preparing a solid composite electrolyte containing sodium-doped modified lithium ferrous silicate filler according to claim 5, characterized in that: In step S2-2, the thickness of the obtained solid composite electrolyte is 80-110 μm.

9. The method for preparing a solid composite electrolyte containing sodium-doped modified lithium ferrous silicate filler according to claim 5, characterized in that: In step S2-1, the uniform mixing method is at least one of magnetic stirring and ball milling; The uniform mixing time is 12-24h.

10. The method for preparing a solid composite electrolyte containing sodium-doped modified lithium ferrous silicate filler according to claim 5, characterized in that: In step S2-2, the drying temperature in the vacuum oven is 60-80°C, and the drying time is 24-48 hours.

Citation Information

Patent Citations

  • Method for preparing sodium-doped lithium ferrous silicate / carbon nano-micro structure composite cathode material

    CN105375013A

  • Composite solid electrolyte and preparation method thereof

    CN116130757A

  • Ion conductor with high room-temperature ionic conductivity and preparation method thereof

    US20220200048A1